A two-dimensional electron gas based on a 5s oxide with high room-temperature mobility and strain sensitivity. (1st February 2021) - Feng, Zexin; Qin, Peixin; Yang, Yali; Yan, Han; Guo, Huixin; Wang, Xiaoning; Zhou, Xiaorong; Han, Yuyan; Yi, Jiabao; Qi, Dongchen; Yu, Xiaojiang; Breese, Mark B.H.; et al.
Abstract: The coupling of optical and electronic degrees of freedom together with quantum confinement in low-dimensional electron systems is particularly interesting for achieving exotic functionalities in strongly correlated oxide electronics. Recently, high room-temperature mobility has been achieved for a large bandgap transparent oxide – BaSnO3 upon extrinsic La or Sb doping, which has excited significant research attention. In this work, we report the realization of a two-dimensional electron gas (2DEG) on the surface of transparent BaSnO3 via oxygen vacancy creation, which exhibits a high carrier density of 7.72 × 10 14 cm −2 and a high room-temperature mobility of 18 cm 2 ·V −1 ·s −1 . Such a 2DEG is rather sensitive to strain and a less than 0.1% in-plane biaxial compressive strain leads to a giant resistance enhancement of 350% (more than 540 kΩ/□) at room temperature. Thus, this work creates a new path to exploring the physics of low-dimensional oxide electronics and devices applicable at room temperature. Graphical abstract: Image, graphical abstract